2002
DOI: 10.1016/s0022-0728(02)00705-2
|View full text |Cite
|
Sign up to set email alerts
|

In situ structural study on underpotential deposition of Ag on Au(111) electrode using surface X-ray scattering technique

Abstract: In situ surface X-ray scattering (SXS) measurements were carried out to study the structure of a Ag layer on a Au(111) electrode formed by underpotential deposition (UPD) in sulfuric acid solution. Specular rod profiles showed that a monolayer of Ag was formed at a potential between the second and third UPD peaks, and a bilayer of Ag was formed at a potential between the third UPD peak and bulk deposition. Non-specular rod profiles demonstrated that electrochemically deposited Ag atoms both in the first and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 29 publications
7
69
0
1
Order By: Relevance
“…It was then transferred to an electrochemical cell with the surface being covered with a drop of ultrapure water to avoid any surface contamination. Upd Ag layers on the Au(111) electrode surface were prepared in a 50 mM H 2 SO 4 solution containing 1 mM Ag 2 SO 4 as previously reported [29] by scanning the potential from 650 mV (Ag/Ag + ) to 50 mV and 10 mV, where Ag upd pseudomorphic mono-and bi-layers, respectively, are known to be formed on a Au(111)-(11) surface [29]. The electrode was then washed with ultrapure water, dried by blowing ultrapure N 2 gas, and then transferred to an SXS cell through ambient atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was then transferred to an electrochemical cell with the surface being covered with a drop of ultrapure water to avoid any surface contamination. Upd Ag layers on the Au(111) electrode surface were prepared in a 50 mM H 2 SO 4 solution containing 1 mM Ag 2 SO 4 as previously reported [29] by scanning the potential from 650 mV (Ag/Ag + ) to 50 mV and 10 mV, where Ag upd pseudomorphic mono-and bi-layers, respectively, are known to be formed on a Au(111)-(11) surface [29]. The electrode was then washed with ultrapure water, dried by blowing ultrapure N 2 gas, and then transferred to an SXS cell through ambient atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Underpotential deposition (upd) is one of the best techniques to prepare ultrathin metal films on single crystal electrode surfaces with well-defined atomic arrangements [1][2][3]. The potential dependent structures of upd metal films with atomic resolution have been studied in situ by scanning tunneling microscopy (STM) [1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], atomic force microscopy (AFM) [22,23], and surface X-ray scattering (SXS) [24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical deposition of Ag on Au(111) electrode surface is a good model system to study the morphology of the deposited layer because the interaction and the lattice misfit between a metal deposit and a substrate is very strong and negligibly small (0.4 %), respectively [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and has been studied by a wide variety of techniques, including scanning tunneling microscopy (STM) [1,2,5,8,9,14,16], atomic force microscopy (AFM) [3,4,6], second harmonic generation (SHG) spectroscopy [13], quartz crystal microbalance (QCM) [7], X-ray diffraction [11,12] and extended X-ray absorption fine structure (EXAFS) [10]. In particular underpotential deposition (UPD) of Ag has received special attention and the structures of adsorbates, both metal and anion, and their dependencies on the potential and electrolyte composition have been well studied [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In particular underpotential deposition (UPD) of Ag has received special attention and the structures of adsorbates, both metal and anion, and their dependencies on the potential and electrolyte composition have been well studied [2][3][4][5][6]. It has been reported that UPD Ag layer of various coverage up to two monolayer is formed depending on the electrode potential [14,15]. Reports on the overpotential deposition (OPD) of Ag on a Au(111) surface are, however, very limited [9,14].…”
Section: Introductionmentioning
confidence: 99%